The Relationship of Breastfeeding Self Efficacy with the Success of Exclusive Breastfeeding in Babies Aged 6 – 12 Months - Rahmawati, Dwi (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: The coverage of exclusive breastfeeding in Indonesia, including in Jambi Province, is still below the national target. In 2022, exclusive breastfeeding coverage in Jambi Province only reached 27.14%, a sharp decrease from 64.67% in the previous year. One of the psychological factors that affect the success of exclusive breastfeeding is the mother's self-efficacy in breastfeeding. Objective: To determine the relationship between the self-efficacy of breastfeeding and the success of exclusive breastfeeding in mothers with babies aged 6–12 months. Methods: This study is a descriptive analytical study with a cross-sectional approach. Data collection was carried out in March 2024 at PMB Azimah and PMB Zulfiatun Rangkuti, Jambi City, with a sample of 45 postpartum mothers selected through a total sampling technique. Data were collected using the Breastfeeding Self-Efficacy Scale–Short Form (BSES-SF) questionnaire and the exclusive breastfeeding questionnaire, then analyzed using the chi-square test with a significance level of α = 0.05. Results: As many as 57.78% of mothers managed to provide exclusive breastfeeding. There was a significant relationship between the self-efficacy of breastfeeding and the success of exclusive breastfeeding (p = 0.004). Conclusion: The higher the mother's confidence in breastfeeding, the greater the chance of success in exclusive breastfeeding. Continuous interventions to improve maternal self-efficacy need to be carried out by health workers to support the success of exclusive breastfeeding programs.